Analisis Manajemen Keuangan Syariah Pada Koperasi Syariah Studi Kasus Bmt Al Ishlah Tahun 2021-2022 Kota Jambi - Nurwiji Asih,; Efni Anita ,; Victor Diwantara , (Jurnal Publikasi Ilmu Manajemen, 2023)
This study aims to find out how the Islamic financial management system is at the BMT Al Iishlah Sharia Cooperative, Jambi City, what are the constraints faced in managing Islamic finance at the BMT Al Iishlah Sharia Cooperative, Jambi City.This research is a type of field research that uses a qualitative descriptive approach. Data collection methods used in this research are observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, verification, and drawing conclusions.Based on the results of research on the manager or managers of BMT Al-Iishlah Jambi City and members of the financing, it shows that the borrower is incompetent, the management is not good or neat, the financial reports are incomplete, the use of funds is not in accordance with planning. , planning is immature, and funds are not sufficient, efforts to anticipate the causes of problematic financing of BMT Al-Ishlah are quite good. The BMT Al-Ishlah Cooperative complies with Islamic guidelines, and complies with the provisions of the Kopeirasii and Peirleimei laws. The management system at BMT Al-Ishlah uses a profit sharing system or mudharabah ratio at the end of each month, so that its financial management activities do not contain elements of usury.